EVALUASI TARGET DAN REALISASI PENCAPAIAN PAJAK DAERAH PADA BADAN PENDAPATAN DAERAH PROVINSI SULAWESI UTARA - Takahindangen, Eka A.; Morasa, Jenny; Runtu, Treesje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
Tax is the main source of state revenue. According to Law No. 28 of 2009 concerning PDRD, regional taxes are mandatory for regions that are owed by individuals or bodies related to legislation, by not obtaining direct imbalances and being used for regional needs for the greatest prosperity of the people. The regional government has agreed to collect regional taxes in order to contribute to the regions to increase the ability of funds in their regions. The purpose of this study is to find out the desired targets motorized vehicles, land tax air tax and percentage of motor vehicle tax, name transfer tax, motor vehicle fuel tax, surface water tax and cigarette tax in the North Sulawesi Provincial Revenue Agency for 2014-2017 have been efficient and effective in North Sulawesi Province. The data analysis method used in this study is descriptive. The results of the analysis of Realization of Regional Taxes in North Sulawesi increase every year, in 2014-2017 the highest income tax is cigarette tax. The results of this study were issued by the regional government of North Sulawesi Province further authorizing the District / City Government to work and be responsible for working in accordance with the duties and functions of administering taxes from the community.